Cuff overinflation and endotracheal tube obstruction: case report and experimental study - Hofstetter, Christian; Scheller, Bertram; Frank, Sandra; Mack, Martin G.; Zwissler, Bernhard; Byhahn, Christian (Scandinavian journal of trauma, resuscitation and emergency medicine, 2010)
Initiated by a clinical case of critical endotracheal tube (ETT) obstruction, we aimed to determine factors that potentially contribute to the development of endotracheal tube obstruction by its inflated cuff. Prehospital climate and storage conditions were simulated.